İslam hukukunda şuf’a hakkı - Akyüz, Şefik (My University, 1999)
ŞUF'A HAKKI Şuf'a hakkı, sahibine satım akdine konu olan akarı, müşteriye mal olduğu bedel karşılığında mülkiyetine geçirme yetkisi veren bir hakkı ifade eder. Temel dayanağı sünnet olan şuf'a hakkı, mülkiyet hakkının dolaylı bir takyidi olup, aynî mahiyette yenilik doğuran bir haktır. Tarihte pek çok devletin Hukuk Sistemi'nde yer aldığı gibi, İslam Hukuku'nda da şuf'a, önemli bir müessese olarak karşımıza çıkmaktadır. Temel amacı, ortakların ve komşuların arasına istenmeyen kişilerin girmesini engellemektir. İslam Hukukçları'nın çoğunluğuna göre, şuf'a hakkı sadece akarlarda câridir. Yine, çoğunluğa göre şuf'a hakkı, sadece bir akarın ortakları arsında câri iken, Hanefiler'e göre, bunun yanı sıra bir akarın irtifak muhtevalı bazı haklarından beraber istifade edenler ve bitişik komşular arasında da câridir. Şuf'a hakkının doğması ve kullnılabilmesi için bazı şartların gerçekleşmesi gerkir: Şuf'a hakkının söz konusu olduğu akar, satım gibi ıvazlı bir akde konu olamlı ve akar, sahibinin mülkiyetinden sahih bir akitle ve kesin bir şekilde çıkmalıdır. Meşfu akar satıldığında, şuf'a sebebi olan akar, şuf'a hakkı sahibinin mülkiyetinde bulunması gerekir. Şuf'a hakkının sahibi, satım akdini duyar duymaz hakkını kullanmalıdır. Hakkın kullanılmasından sonra, müşteri kendi rızası ile meşfu akarı hak sahibine vermezse, şuf'a davası açılabilir. Şuf'a hakkının kullanılması ile, şefi ile müşteri arasında yeni bir satım ilişkisi doğar. Meşfu akardan, hak sahipleri, Hanefiler'e göre eşit olarak; cumhura göre, hisseleri oranında yararlanırlar. Şuf'a hakkı, usulüne göre kullanılmazsa veya haktan vaz geçilirse, ortadan kalkar. THE RIGHT OF SHUFAA (PRE-EMPTION) Pre-emption is a right which the owner of a real-estate possesses to acquire by purchase another immovable property which has been solt to another person. Pre-emption, which based on the Sunna of Mohammed, is an idirect restiriction on the right of ownership and also it creates new conditions in the same context. In the historical recourse, as pre-emption has taken places in the legal system of many states, it is also one of the importent foundations of Islamic Law. Its main aim is warding off strangers from one's neighboorhood or preserving family heritage. According to the majority of the Islamic Juridts, pre-emption is valid only on real-estate. There are also controversies among the scholars about the same matter; while validity of the right of pre-emption is realized among only co-sharers of a real-estate for majorities, according to Hanefi Law, pre-emption can apply only to those who benefit from the relations of the rihgts of accession and to those who are the immediate neighboors of it. The right of Shufaa arises and becomes usable only on ground that the real-estate, on which pre-emption attachs, should be considered as sale subject and the real-estate should be released definitly from the possession of the owner with an accurate agreement. When the immovable property was sold, it should be also in the possession of the pre-empter. Just as the sale contract is realized, the pre-empter should use his/ her rihgt. If the property isn't given to the owner after the right has been used, he/ she can bring a suit for pre-emption, consequently a new sale relation exists among the seller and purchaser. Those who are co-sharers of a real-estate can benefit from it equally according to Hanafi Law, where as for the majority of the scholars, the co-sharers can benefit from it in respect to their sharer. If the right of the pre-emption isn't used along its proper proce dure or in the case of relinquishment, it is extinquisyhed.
Keywords: Din; Fıkıh ve fıkıh ilmi; İslam Dini; İSLAM HUKUKU; MÜLKİYET HAKKI